Gut and Liver B Cells of Common Clonal Origin in Primary Sclerosing Cholangitis–Inflammatory Bowel Disease - Brian K. Chung; Eva Kristine Klemsdal Henriksen; Kristin Kaasen Jørgensen; Tom H. Karlsen; Gideon M. Hirschfield; Evaggelia Liaskou (Hepatology Communications, 2018)
B cells express an antigen‐specific B‐cell receptor (BCR) and may contribute to liver inflammation by recognizing shared antigens in the gut and liver. Herein, we used high‐throughput BCR sequencing of the immunoglobulin heavy chain, specifically the complementarity‐determining region 3 (CDR3), to characterize the B‐cell repertoire of freshly‐frozen paired gut and liver tissue samples from patients with primary sclerosing cholangitis (PSC) and concurrent inflammatory bowel disease (IBD) (PSC‐IBD, n = 10) and paired formalin‐fixed paraffin‐embedded (FFPE) tumor‐adjacent normal colon and liver tissue from patients with colorectal liver metastases (controls, n = 10). We observed significantly greater numbers of B cells (P < 0.01) and unique B‐cell clonotypes (P < 0.05) in gut samples compared to liver samples of patients with PSC‐IBD, whereas BCR sequences in FFPE normal gut and liver samples were nearly absent (14 ± 5 clonotypes; mean ± SD; n = 20). In PSC‐IBD, an average of 8.3% (range, 1.6%‐18.0%) of B‐cell clonotypes were found to overlap paired gut and liver samples following the exclusion of memory clonotypes reported in the blood of healthy controls. Overlapping gut and liver clonotypes showed stronger evidence of antigen‐driven activation compared to non‐overlapping clonotypes, including shorter CDR3 lengths and higher counts of somatic hypermutation (P < 0.0001). Conclusion: A proportion of gut and liver B cells originate from a common clonal origin (i.e., likely to recognize the same antigen) in patients with PSC which suggests B‐cell antigens are shared across the gut–liver axis. (Hepatology Communications 2018; 00:000‐000)